Impacts of Manual Handling Training and Lifting Devices on Risks of Back Pain among Nurses: An Integrative Literature Review - Aljohani, Wael Abdullah; Pascua, Glezzeelyne Pascual (Nurse Media Journal of Nursing, 2019)
Background: Musculoskeletal injuries, notably lower back injuries, are major occupational health problems among nurses. These injuries occur mainly due to incorrect use of body mechanics upon handling, lifting, and transfer of patients. It is the leading cause of occupational disability and is associated with increased healthcare costs. Reducing these injuries can lead to a significant reduction in healthcare costs.Purpose: This integrative literature review aims to examine the impacts of manual handling and lifting devices on the risk of back pain among hospital nurses.Methods: This study uses an integrative literature review design. Proquest, Science Direct, MEDLINE, and CINAHL were searched comprehensively. A Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) flow diagram was used to check the number of publications that were identified and screened for eligibility, and the number of publications excluded and reasons for exclusion. The Critical Appraisal Skills Programme (CASP) and the Centre for Evidence-Based Management critical appraisal checklist for a cross-sectional study (CEBM) were used to appraise the quality of selected articles.Results: Fifteen studies were found to highlight the importance of manual handling training programs and the consistent use of lifting devices in the prevention of low back pain. Ergonomics training, proper body mechanics and posture, use of body slings, workplace characteristics, availability of equipments and complexity of work, lost work days including nurses’ knowledge, experience, attitude and compliance are essential factors that impacts back pain.Conclusion: Manual handling training programs and the use of patient lifting equipment are effective in preventing lower back pain among nurses.